Hubungan Motivasi Perawat Dengan Pendokumentasian Asuhan Keperawatan di Instalasi Rawat Inap (IRNA) A Rsud Raden Mattaher Jambi - Leni Putri; Yusnilawati Yusnilawati; Indah Mawarti (LPPM Institut Pendidikan Nusantara Global, 2026)
Background:Nursing documentation is an essential component of nursing care as evidence of nurses’ professional accountability, an indicator of service quality, and a basis for clinical decision-making. A preliminary survey conducted at Raden Mattaher Regional General Hospital, Jambi, indicated that non-compliance among nurses in completing nursing care documentation still exists. This study aimed to determine the relationship between nurses’ motivation and the quality of nursing care documentation in Inpatient Installation A (IRNA A) at Raden Mattaher Regional General Hospital, Jambi. Methods: This study employed a cross-sectional design with a total sampling technique, involving 112 nurses and 87 nursing care documents. Data were collected using a nurses’ motivation questionnaire and an observation checklist based on Instrument A of the Indonesian Ministry of Health, in accordance with the Indonesian Nursing Diagnosis Standards (SDKI), Indonesian Nursing Intervention Standards (SIKI), and Indonesian Nursing Outcome Standards (SLKI). Univariate analysis was performed using frequency distributions, while bivariate analysis was conducted using the Spearman rank correlation test. Results: The results showed that most nurses had high motivation (91.1%), and most nursing care documentation was complete (64.3%). Statistical analysis demonstrated a significant relationship between nurses’ motivation and the completeness of nursing care documentation (p = 0.000; ρ = 0.487). It can be concluded that higher nurse motivation is significantly associated with more complete nursing care documentation. Therefore, efforts to improve nurses’ motivation through regular supervision and continuous training are strongly recommended to enhance the quality of nursing documentation.